Exploring Research Trends in the Indonesian Archipelago’s New National Capital - Hamjen, Hilarion; Said, Laila Refiana (Journal of International Conference Proceedings, 2023)
The Indonesian Government announced the relocation of the National Capital from Jakarta to East Kalimantan Province in 2019. The term ‘Capital of the Archipelago ' or Ibu Kota Nusantara (IKN) was approved as the name of the new capital of the Republic of Indonesia. This study conducted visualization and bibliometric analysis using VOSviewer 1.6.20 from 100 scientific articles with the keyword "Ibu Kota Nusantara" collected from Google Scholar. The frequency of article titles relevant to IKN in 2022 was greater than in 2023. In the comparison of titles with the term IKN in 2022, there were 22 articles; in 2023, there were 15 articles, so the difference was 22/15 or 1.467. Following the 12 images of IKN, there were five images related to some scientific articles that have been published, including those related to innovation and technology where IKN was imaged as a smart city, sustainable capital, environmentally friendly, green city, and greening. However, seven images need attention for the following research topics: renewable, legal, cultural, user-friendly road, unique, city of change, and solutions for equality. This study helps provide insight as a basis for further research on various innovative themes related to IKN.